Triangle Support for Live Maintenance of 20 kV Distribution Lines: Penyangga Segitiga untuk Pemeliharaan Langsung Saluran Distribusi 20 kV - Hairul Ismail; Jamaaluddin Jamaaluddin (Academia Open, 2025)
General Background: Reliable electricity supply is a fundamental requirement for societal productivity, requiring distribution network maintenance strategies that minimize service interruptions. Specific Background: Live-line maintenance using PDKB distance and direct contact methods on 20 kV medium-voltage overhead lines remains constrained by task-specific equipment, resulting in operational inefficiency, worker fatigue, and continued reliance on outages for certain constructions such as double insulator pedestal and double strain insulator. Knowledge Gap: Economic analyses of multifunctional maintenance equipment capable of supporting multiple PDKB tasks without power outages are still limited, particularly for integrated tools applied to diverse construction configurations. Aims: This study aimed to analyze the economic application of the Triangle Support tool for maintenance of double insulator pedestal and double strain insulator constructions on 20 kV distribution lines without grid outages. Results: The Triangle Support, configurable into three arrangements, enabled 16 types of PDKB tasks, including seven activities previously requiring outages, while generating energy savings of 191,422 kWh and additional company revenue of IDR 217,455,773 due to reduced completion time. Novelty: The research introduces a modular triangular support system integrating multiple live-line maintenance functions within a single tool supported by cost–benefit analysis. Implications: The findings indicate that adoption of Triangle Support can reduce outage frequency, improve operational continuity, and provide measurable economic benefits for power distribution maintenance services. Highlights: A Single Modular Device Accommodated Multiple Distance and Direct Contact Maintenance Tasks. Several Activities Previously Requiring Outages Were Shifted to Live-Line Procedures. Measurable Energy Savings and Additional Revenue Resulted From Shorter Job Duration. Keywords: Triangle Support, Live-Line Maintenance, 20 Kv Distribution Network, Pdkb Methods, Economic Analysis